The Role of Strategic Collaboration on the Capacity Development in Central Sulawesi Province in Indonesia - Tahili, Mashuri H.; Halim, Rahmawati; Haris, Subhan; Djaelangkara, Rizali; Rafika, Ika (Journal Management & Economics Review (JUMPER), 2025)
A strategy collaboration approach is an appropriate system used by an organization to structure the way a team works, which is based on solid teamwork and developing capabilities which including the improvement of collaboration strategies within the organization. This study was employed to investigate the role of strategic collaboration approaches on developing the capacity development in basic education in Indonesia. The study applied the sequential mixed methods, which have a total sample of 350 respondents in Central Sulawesi Province, Indonesia. This study used quantitative analysis through questionnaires. This analysis uses Norris-Tirrell & Clay Theory, which involves four analyses such as strategic collaboration planning, collaborative leadership development, stakeholder collaboration capacity, and interorganizational collaboration. The study found that the four dimensions of strategic collaboration have influenced capacity development in basic education; there must be more challenges for the strategic collaboration to be a greater strategy for developing the capacity development, especially in basic education in Indonesia.